(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2023)
A field experiment was carried out at the research farm of Charfasson Govt. College, Bhola, Bangladesh in rabi season in 2015-2016 to evaluate the effects of cow dung (CD) with and without NPK fertilizers to estimate the concentration, uptake and oil content of sunflower cv. BARI-2 (Keroni-2). It was laid out in a completely randomized block design (CRBD) having sixteen treatments with three replications and plot size was 3m×2m. Treatments were T1: Control (- CD and -NPK), T2: 2.5t CD ha-1, T3: 5t CD ha-1, T4: 7.5t CD ha-1, T5: N40P30K50kg ha-1, T6: N80P60K100kg ha-1, T7: N120P90K150kg ha-1, T8: 2.5t CD ha-1 +N40P30K50kg ha-1, T9: 2.5t CD ha-1+N80P60K100kg ha-1, T10: 2.5t CD ha-1+N120P90K150kg ha-1, T11: 5t CD ha-1+ N40P30K50kg ha-1, T12: 5t CD ha-1+N80P60K100kg ha-1, T13: 5t CD ha-1 +N120P90K150kg ha-1, T14:7.5t CD ha-1+N40P30K50kg ha-1, T15:7.5t CD ha-1+N80P60K100kg ha-1 and T16: 7.5t CD ha-1+N120P90K150kg ha-1. Sixty plants were grown in each plot for 90 days. Maximum values of NPKS concentration (%) in different organs of sunflower were 1.08, 0.38, 2.04, 0.18 for root; 1.33, 0.33, 1.85, 0.19 for stem; 3.45, 0.67, 4.12, 0.18 for leaf; 1.99, 0.62, 3.0, 0.22 for petiole; 0.73, 0.68, 2.25, 0.23 for inflorescence, and 4.95, 0.94, 0.75, 0.26 for seed measured in combined treatments of 5t CD ha-1 + N120P90K150kg ha-1 and 7.5t CD ha-1 + N120P90K150kg ha-1 in most of the cases. The uptake pattern also followed the same trend as in concentration. The lowest concentration and uptake of NPKS were recorded in control (-CD and -NPK). The highest content of oil in seed (51.8%) was extracted from the treatment 5t CD ha-1+ N120P90K150kg ha-1 and the lowest value (35.6%) was in treatment 5t CD ha-1+ N80P60K100kg ha-1 which was lower than control. The findings of this study indicated that cow dung in combination with chemical fertilizers enhanced the concentration and uptake of NPKS and oil content in seeds of sunflower. The dose 5t CD ha-1 +N120P90K150kg ha-1 can be suggested to produce maximum oil. Study generated an information for the concern people for future research. J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(2): 51-60